The Effect of Descending Resources Reform on Reallocating Healthcare Resources: An Analysis Based on the Difference-in-Differences Method - Chenyi Yang Master; Zesheng Sun PhD; Shuyun Wang PhD; Yuqing Shen Master; Shuhong Wang PhD (SAGE Publishing, 2023)
Since 2010, China has been exploring descending resources reform in order to correct the imbalanced allocation of healthcare resources and promote coordinated economic development among regions. This paper for the first time estimates the impact this reform has had on the reallocation of healthcare resources by using prefecture-level cities panel data from Zhejiang Province, China, which implemented the reform province-wide in 2013. The time-varying difference-in-differences (DID) method was used to estimate the reform's policy effects. The data used in this paper is from published statistical yearbooks and local governments, which include panel data from 11 prefecture-level and higher cities in Zhejiang Province as the treated group and 46 prefecture-level cities in Jiangsu, Henan, and Sichuan Province as the control group. The entropy weight method was used to construct the supply index and demand index to incorporate multiple inputs and outputs, and efficiency indicators were constructed using the ratio method. This research found that the reform has had a positive effect on outpatient visits in different prefecture-level cities with vast rural areas. However, this reform exerted no significant impact on inpatient services or supply-side or resource allocation efficiency. Several robust tests support the above conclusions, and one theoretical explanation is provided. The descending health resources reform can be a valuable reform path in promoting more balanced healthcare resource allocation; however, the resultant disparities in its effects should be considered when implementing it.